INCIDENCE AND PREVALENCE OF CHAGAS DISEASE IN BRAZIL (CIPEEX, 2022)
CHAGAS' DISEASE (DC), ALSO KNOWN AS AMERICAN TYRANNATOSIS, IS A PARASITIC DISEASE TRANSMITTED BY THE PROTOZOAN TRYPANOSOMA CRUZI, PRESENT IN THE FECES OF THE VECTOR MOSQUITO TRIATOMA INFESTANS, RELEASED AFTER STINGING. THUS, IN ORDER TO CARRY OUT A LITERATURE REVIEW, 5 ARTICLES WERE ANALYZED THAT ADDRESSED THE THEME OF CD IN THE DIFFERENT BRAZILIAN REGIONS, THROUGH THE PLATFORMS PUBMED, SCIELO AND GOOGLE ACADEMIC, WITH THE AIM OF PORTRAYING THE PANORAMA OF THE INCIDENCE AND PREVALENCE OF CHAGAS DISEASE IN THE COUNTRY. THUS, ONE CAN CONCLUDE THAT BRAZIL IS ONE OF THE MAIN ENDEMIC FOCI OF CHAGAS' DISEASE IN LATIN AMERICA, ALTHOUGH DATA ON INCIDENCE AND PREVALENCE HAVE DECREASED OVER THE YEARS, GENERATING BOTH A HYPOTHESIS OF CASE REDUCTION AND THE LACK OF RESEARCH.
Keywords: Trypanosoma cruzi. Chagas disease. Triatoma infestans.